Fractal Based Antenna Size Reduction Examined by Numerical Methods - Pólik, Z. (Acta Technica Jaurinensis, 2011)
Koch curve based dipole antennas have been built up, have been simulated and have been measured to examine the reachable size reduction. The simulations have been performed by using the method of moment (MoM) and the finite element method (FEM). The Pocklington integral equation and the ATW EFIE method have been deduced and have been implemented in MATLAB environment to simulate dipole antennas and arbitrary shaped thin wire antennas. In COMSOL Multiphysics software environment a finite element model has been set up to solve the Helmholtz equation and to simulate the antennas under examination. Koch curve based dipole antennas have been measured in a full anechoic chamber, as well. The numerical and the experimental results have been compared with the outcome of other softwares.